ANALISIS PDRB PROVINSI SUMATERA UTARA: PENDEKATAN LOCATION QUOTIENT, SHIFT SHARE, DAN INDEKS WILLIAMSON PERIODE 2020-2024 - Ratu Ayu Thalia Salsabina; I Wayan Suparta; Astrisya Nadine; Amanda Audila; Syavira Aulia Kurniawan; Olivia Andarisca Putri; Ikhsan Bintang Aswangga; Ilham Arvindo (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this research is to identify the base sectors, analyze sectoral growth, and measure development disparities between regions in North Sumatra Province for the period 2020–2024 using the Location Quotient (LQ), Shift-Share, and Williamson Index approaches. The data is sourced from the North Sumatra Provincial Statistics Agency (BPS). The results of the study confirm that the manufacturing, trade, and real estate sectors are considered base sectors, with LQ values greater than 1. The Shift-Share analysis indicates that sectoral growth is driven primarily by national growth, with the agriculture sector exhibiting the highest local competitiveness. The average Williamson Index is 0.435, indicating a moderate level of inequality that tends to increase, with the largest disparity between Medan City and South Nias Regency. This research recommends accelerating infrastructure development in remote areas, downstreaming of flagship commodities, and increasing investment in underdeveloped regions.